Synthesis of stable isotope‐labelled firocoxib. (5th May 2020) - Latli, Bachir; Gao, Amy; Kvaternick, Valerie; Tecle, Berhane; Pennino, Scott; Yee, Nathan K.; Song, Jeff
Abstract : Firocoxib (ML‐1, 785, 713) is a nonsteroidal, potent, and selective COX‐2 inhibitor, approved for the control of pain and inflammation associated with osteoarthritis in dogs and horses, as well as to control postoperative pain and inflammation in dogs. We employed a six‐step synthesis to prepare firocoxib‐[ 13 C6 ] in an overall yield of 35% from the commercially available bromobenzene‐[ 13 C6 ]. The synthetic route involved the preparation of the key intermediate phenyl‐ 13 C 6 ‐methyl sulfide using cesium carbonate and S‐ methylthiourea sulfate under transition‐metal free conditions. A two‐step preparation of firocoxib‐[ 13 C, 2 H3 ] via the sulfinic acid derivative of firocoxib and methyl iodide‐[ 13 C, 2 H3 ] using the procedure of Gauthier and Yoshikawa was first undertaken. However, the deuterium atoms of the methyl sulfone undergo extensive exchange in aqueous media even at neutral pH. The isotope‐labelled firocoxib is intended as an internal standard for bioanalyses of firocoxib from biological matrices. Abstract : Firocoxib is a nonsteroidal, potent, and selective COX‐2 inhibitor, approved for the control of pain and inflammation associated with osteoarthritis in dogs and horses. A six‐step synthesis was used to prepare firocoxib‐[ 13 C6 ] in an overall yield of 35% from the commercially available bromobenzene‐[ 13 C6].